Poetics of the philological novel dy A. Siniavsky/A. Tertz - A S Karpov (RUDN Journal of Studies in Literature and Journalism, 2012)
The article gives us characteristics of the poetics peculiarities of works by A. Siniavsky/A. Tertz belonging to the philological prose where thought development of the researcher goes in the forms related to fiction literature.